Pengaruh Rasio Leverage, Kepemilikan Manajerial dan Kepemilikan Institusional terhadap Penghindaran Pajak (Tax Avoidance) pada Perusahaan Manufaktur BEI Tahun 2019-2021 - Zakaria, Muh Azhar; Muid, Dul (Universitas Katolik Soegijapranata, Semarang, 2024)
The economic aspect that greatly impacts the income and revenue of the state is taxes. The practice of reducing or minimizing the tax burden carried out in accordance with tax regulations and laws is called Tax Avoidance. The purpose of this study is to examine whether there is a relationship between leverage (DER), managerial ownership and institutional ownership on tax evasion. This study uses a purposive sampling method, a quantitative approach and uses secondary data by collecting data on manufacturing companies in the various industrial sectors for the 2019-2021 period on the IDX.The results of this study prove that the leverage ratio (DER) has no significant effect on tax avoidance. Managerial ownership has no significant effect on tax avoidance and institutional ownership has a positive effect on tax avoidance. Data analysis used in this study was carried out using Statistical Package for Social Science (SPSS) version 26. This study used a sample of 63 data from 21 manufacturing companies in the various industrial sectors from 2019 to 2021